"All for Love, and Nothing for Reward, ": Psyche from Spenser to Lacan, and the Loss of Critical Values. Issue 2 (November 2016) - Martin, Thomas L.; Pesta, Duke
Abstract : As a generation of Lacanian critics convert what Spenser does into a science of the formations of subjectivity and psycholinguistic desire, they miss Spenser's project of providing a unique account of human psychology in his encyclopedic work. Both Lacan and Spenser have detailed accounts of the operations of the human soul or psyche and the stages the subject passes through in each. As the essay contrasts these divergent models, a number of illuminating distinctions emerge. While in Lacan the self remains positioned in a single arena where the irreconcilable demands of subjectivity and intersubjectivity oppose one another perpetually, in Spenser the conditions of subjectivity are always perilous for the self, cut off from the nutriments of community and nature. Despite grand claims Lacanians have made on his behalf, Lacan's account of human nature cannot enter the heroic struggles of Spenser's second stage and so never fully engages the dynamics of Spenser's quest narrative. The story Lacan tells of the psyche is always the one that ends in a tragic thwarting. Whether we like Spenser's picture or not, it is clearly not the one espoused by Lacan. In the end, a comparative critical reading of Spenser helps correct an interpretive overeagerness by Lacanian critics, a cast of mind that is perhaps psychologically significant in itself. Spenser's cautionary tales about the pitfalls of subjectivity and its proper correctives outside the self contrast finally with a style of reading that mirrors the critics' own narcissistic obsessions more than they are willing to admit.